Madrasah Quality Improvement Evaluation Strategic Management Based - Hary Priatna Sanusi (International Journal of Nusantara Islam, 2020)
This study was motivated by a phenomenon that appears in madrasa, namely: 1) the low quality of graduates, in MAN 1 with an average result of UAN 58.5 and MAN 2 57.8 from a maximum score of 100; 2) inconsistency in planning, implementing, evaluating programs to improve quality. The purpose of this study was to identify: work programs, program implementation, evaluation of program implementation, program impacts, and supporting factors inhibiting the improvement of the quality of madrasa. The approach of this study was qualitative-naturalistic, with a descriptive research type. This research method was a case study, with data collection techniques through interviews, observation, and documentation study. Meanwhile, the data analysis technique used the interactive Miles model. The results of this study showed: evaluation of quality improvement which is carried out through an evaluation of needs assessment, assessment of input, assessment of processes and assessment of results.